THE RELATIONSHIP KNOWLEDGE AND ATTITUDE OF PREGNANT WOMEN IN FULFILLING NUTRITION NEEDS WITH NUTRITIONAL STATUS IN RAYA PUSKESMAS, RAYA DISTRICT - Yunardi (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2021)
Nutritional status is a measure of success in fulfilling nutrition for pregnant women. Nutrition for pregnant women is the nutrition needed in large quantities to fulfill the nutrition of the mother herself and the development of the fetus she contains. Fulfilling the nutritional needs of pregnant women is closely related to the level of maternal knowledge about nutrition during pregnancy. Meanwhile, the attitude of the mother in fulfilling the needs is what is seen and known by the mother in fulfilling nutritional needs through information. Correlation descriptive research method using primary data through a questionnaire based on the knowledge and attitudes of pregnant women. The sampling technique in this study was purvosive sampling, that is, the researcher determined the sample taken because of certain considerations. From the results of this study it was concluded that there was no relationship between knowledge of pregnant women in fulfilling nutritional needs with nutritional status at the Raya Public Health Center, Raya District, Simalungun Regency, this was evidenced by the results of the chi-square test with a p-value = 0.163 and there was a relationship between attitudes of pregnant women in meet nutritional needs with nutritional status at the Panombeian Panei Health Center, Panombeian Panei District, Simalungun Regency in 2016, this is evidenced by the results of the chi-square test with a p-value = 0.004. Pregnant women are expected to have more regular check-ups for their pregnancies with health workers and actively participate in counseling conducted by health workers to obtain information related to nutrition during pregnancy.